A longitudinal analysis of technical-tactical and physical performance of the teams in the Spanish LaLiga Santander: An eight-season study - Errekagorri, I.; Castellano, J.; Echeazarra, I.; López-Del Campo, R.; Resta, R. (Biology of Sport, 2022)
The aim of this study was to describe in the way teams played for the last eight seasons (from 2011-12 to 2018-19) in the Spanish Football First Division (Spanish LaLiga Santander), taking into account team match performances (n = 5,518). Ten technical-tactical and physical variables grouped into five dimensions were used: final behaviour (shots and crosses), set piece (corners and fouls), match volume (passes), physical performance (total distance covered) and collective use of the space (team width, team length, team defence height and distance from the goalkeeper to their defence). The main results were that the number of passes and team width showed a stable trend as the seasons passed. Nevertheless, the number of shots, crosses and corners, total distance covered, team length and distance from the goalkeeper to their defence showed a descending trend. The main conclusion was that over the seasons studied, the Spanish LaLiga Santander teams were characterized by an indirect style of play that, being the usual in this league, presented some evolution. The trend in the evolution of the game is that defence is put before attack. The findings of the study may be of interest to professional football staff to know more about the particular way teams play in competition, as well as its evolution, so as to focus on the training process according to the trend that is taking place in the game.